Analisis karakteristik pirolisis limbah plastik low density polyetylene (LDPE) sebagai bahan bakar alternatif - Andika Wisnujati; Ferriawan Yudhanto (Universitas Muhammadiyah Metro, 2020)
Plastic bag waste in Indonesia is very alarming. The many uses of plastic bags and those made from plastic in the food sector, industry, and others will have a bad impact on the environment if it carried out continuously and the utilization of waste plastic bags. This research was conducted by utilizing waste plastic bags Low-Density Polyethylene (LDPE) to be converted into fuel oil by the pyrolysis process. Starting from the design and manufacture of pyrolysis devices, the process of pyrolysis for extracting fuel oil, and laboratory testing of oil density, oil viscosity, and oil calorific value. Pyrolysis was carried out three times with heating temperatures varying at 200°C, 250°C, and 300°C. This research concludes that pyrolysis oil of LDPE plastic bag waste that can be used for alternative fuels in this research can be ignited through a spark at a heating temperature of 250 ° C with a viscosity of 1.95 cP, a calorific value of 10826.388 cal/gr, and an oil density of 0.7044 gr/mlKeywords: plastic, pyrolysis, fuel oil, alternative energy.